From Operation to Action: Process-Orientation in Interpreting Studies - Pöchhacker, Franz (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe notion of ‘process’ is identified as a prominent idea in systematic reflection on interpreting, and various incarnations of the ‘process(ing) supermeme’ are reviewed. With reference to selected models of the interpreting process, the need for a broader concept of ‘process’ in interpreting research is discussed, with special reference to the (inter)action-theoretical approach championed by German translation scholars in the 1980s. Based on an interactant model of the interpreting situation, the author highlights the relevance of contextual as well as cognitive factors and suggests ways in which various conceptual approaches can be reconciled to establish a more comprehensive sort of process-orientation in interpreting studies.